First report of Austroporus doctus (Blackburn) from New Zealand and description of its larva (Coleoptera: Phalacridae) - Gimmel, Matthew L.; Leschen, Richard A. B. (Papéis Avulsos de Zoologia, 2020)
The Australian species Austroporus doctus (Blackburn) is reported from New Zealand for the first time. Adults are illustrated and diagnosed, and late-instar larvae are fully described and illustrated. In addition, a summary of prior larval descriptions of Phalacridae is provided. This represents the first description of the morphology and habitat of the larvae within the genus Austroporus Gimmel and the Olibroporus-group of genera. Austroporus doctus is native to eastern Australia, where adults are distinguished from similar species by characters of the male genitalia and by a suite of external morphological features. There are no native members of Phalacridae known from New Zealand, but A. doctus represents the second introduced and established species there. A key is given to differentiate adult and larval A. doctus from the other introduced New Zealand species, Phalacrus uniformis (Blackburn).